Anti-lung cancer effect of paclitaxel solid lipid nanoparticles delivery system with curcumin as co-loading partner in vitro and in vivo - Chao Pi; Wenmei Zhao; Mingtang Zeng; Jiyuan Yuan; Hongping Shen; Ke Li; Zhilian Su; Zerong Liu; Jie Wen; Xinjie Song; Robert J. Lee; Yumeng Wei; et al. (Taylor & Francis Group, 2022)
The main aim of this study was to improve the therapeutic potential of a paclitaxel (PTX) and curcumin (CU) combination regimen using solid lipid nanoparticles (SLNs). PTX and CU were successfully co-encapsulated at a predetermined ratio in SLNs (PC-SLNs) with high encapsulation efficiency (CU: 97.6%, PTX: 95.8%), appropriate particle size (121.8 ± 1.69 nm), small PDI (0.267 ± 0.023), and negative zeta potential (-30.4 ± 1.25 mV). Compared with PTX or the combination of CU and PTX (CU + PTX), PC-SLNs can greatly reduce the dose of PTX while still achieving the same therapeutic effect on four cancer cell lines, among which the inhibitory effect on A549 lung cancer cells was the strongest. PC-SLNs improved the area under the curve (CU: 1.40-fold; PTX: 2.88-fold), prolonged the residence time (CU: 6.94-fold; PTX: 2.51-fold), and increased the half-life (CU: 5.62-fold; PTX: 6.46-fold), achieving long circulation. PC-SLNs were used to treat lung cancer in a nude mouse xenograft tumor model and the tumor suppression rate reached 78.42%, while those of PTX and (CU + PTX) were 40.53% and 51.56%, respectively. As PC-SLNs can prevent P-glycoprotein efflux, reverse MDR and downregulate the NF-κB pathway. PC-SLNs are a potential antineoplastic agent that is more effective and less toxic in treating lung cancer.